A mix design procedure for low calcium alkali activated fly ash-based concretes. (15th March 2015) - Talha Junaid, M.; Kayali, Obada; Khennane, Amar; Black, Jarvis
Highlights: GPC is widely used in construction industry but no formal mix design methods exist. Methods for OPC cannot be used due to dissimilarity in binder chemistry. A framework for formal design of GPC mixes is proposed using established variables. Proposed method presents design aids for GPC mix of variable strength & workability. Highly repeatable method with consistent results and ready for practical use. Abstract: This paper presents a systematic approach for selecting mix proportions for alkali activated fly ash-based geopolymer concrete (GPC). The proposed mix design process is developed for low calcium Class F fly ash activated geopolymers using sodium silicates and sodium hydroxide as activator solutions. A review of the literature reveals that there are no published comprehensive approaches in designing mixes for GPC. In this paper the key factors that determine the characteristics of GPC mix are identified. The authors consider the water to geopolymer solid (W/GPS) and alkaline liquid to fly ash (AL/FA) ratios as direct measures of strength and workability. The ratio of alkaline liquid to water (AL/W) is identified to be most closely linked to the strength of GPC mixes. The paper presents detailed examples of mix designs for various strengths.